Imagen Corporativa en la empresa DISMERO S. A - Vásquez Aguirre, Estefani Liseth (2017)
The commercial was born as idea of ​​emprendimiento in the year 1996, before the necessity to satisfy to the sectors of the cities of Milagro and Babahoyo with the modality of wholesale store that in its first beginnings was attended and directed of direct way by its current majoritarian partner . Initially served sectors such as: the enclosure 3 posts; the canton Juján, until arriving at the city of Babahoyo.